Historia : empiricism and erudition in early modern Europe - Pomata, Gianna; Siraisi, Nancy G. (Transformations (M.I.T. Press), 2005)
Essays examine how the genre of historia reflects connections between the study of nature and the study of culture in early modern scholarly pursuits.